Flat processing of stell - Roberts, William L. (Manufacturing engineering and materials processing, 1988)
"This outstanding reference, packed with nearly 700 illustrations, describes all the various operations involved in the flat processing of steel -- covering everything from the rolling of slabs to the metallic coating of sheet and strip products.